1993
DOI: 10.1346/ccmn.1993.0410107
|View full text |Cite
|
Sign up to set email alerts
|

Illite from the Potsdam Sandstone of New York: A Probable Noncentrosymmetric Mica Structure

Abstract: Abstract--Illite from the Potsdam Sandstone (lower Ordovician) of Northwestern New York was studied by powder X-ray diffraction, scanning electron microscopy, and chemically analyzed and dated by the K/Ar method. The texture and ages of 360 and 392 Ma on two samples establish that the mineral is authigenie and relatively uncontaminated by Precambrian detritus. Random powder X-ray diffraction patterns show sharp and relatively intense 02l and 1 ll reflections, indicating an ordered structure. Comparisons with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…For illite, the most common polytypes are the 1 M d , 1M and 2M 1 (e.g. Reynolds and Thomson 1993). With raising temperature, illite shows irreversible polytype transformation of 1 M d ?…”
Section: Mineralogy and K-ar Dating Of Fault Gougesmentioning
confidence: 99%
“…For illite, the most common polytypes are the 1 M d , 1M and 2M 1 (e.g. Reynolds and Thomson 1993). With raising temperature, illite shows irreversible polytype transformation of 1 M d ?…”
Section: Mineralogy and K-ar Dating Of Fault Gougesmentioning
confidence: 99%
“…Drits et al (1993) noted that the 3T and cv-lM structures produce similar diffraction effects. However, Reynolds and Thomson (1993) found that in determining the structure of the Potsdam illite, the d values of the Potsdam illite could not be reconciled with a hexagonal structure (e.g., 337) and these values are (1984). Indexing was possible because the Potsdam illite has sharp diffraction maxima.…”
Section: Introductionmentioning
confidence: 98%
“…Oblique-texture electron diffraction (OTED) work by Tsipursky and Drits (1984) showed that dioctahedral smectites have a wide range of proportions of cv and tv layers. Reynolds and Thomson (1993) showed that the illite from the Potsdam sandstone of New York has the cv structure and Drits et al (1993) described another occurrence. Reynolds (1992), McCarty (1993), McCarty and Reynolds (1995), and Drits et al (1998) demonstrated that cv structures exist in I-S exhibiting the 1M and 1Md stacking sequences, and that cv 2:1 layers are commonly interstratified with tv layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drits et al (1984a) formulated structural and diffraction criteria to distinguish between dioctahedral 1M micas consisting of cis-vacant (cv 1M) or trans-vacant (tv 1M) 2:1 layers. Based on these criteria, cv 1M illites were found in different geological environments (Zvyagin et al, 1985;Drits et al, 1993a;Reynolds & Thompson, 1993). Conversely, Sakharov et al, (1990) andDrits et al (1993b) studied a large collection of glauconites differing in chemical composition, age, location and structural perfection.…”
mentioning
confidence: 99%